Controlled Synthesis and Characterization of Micrometric Single Crystalline Magnetite With Superparamagnetic Behavior and Cytocompatibility/Cytotoxicity Assessments - Farcas, Claudia Geanina; Macasoi, Ioana; Pinzaru, Iulia; Chirita, Marius; Chirita Mihaila, Marius Constantin; Dehelean, Cristina; Avram, Stefana; Loghin, Felicia; Mocanu, Liviu; Rotaru, Virgil; Ieta, Adrian; Ercuta, Aurel; et al. (Frontiers in Pharmacology, 2020)
A new class of magnetite (Fe3O4) particles, coined as “Single Crystalline Micrometric Iron Oxide Particles” (SCMIOPs), were obtained by hydrothermal synthesis. Both the single Fe3O4 phase content and the particle sizes range, from 1µm to 30 µm, can be controlled by synthesis. The notable finding state that these particles exhibit vanishing remanent magnetization (σr=0.28 emu/g) and coercive force (Hc=1.5 Oe), which indicate a superparamagnetic-like behavior (unexpected at micrometric particles size), and remarkably high saturation magnetization (σs=95.5 emu/g), what ensures strong magnetic response, and the lack of agglomeration after the magnetic field removal. These qualities make such particles candidates for biomedical applications, to be used instead of magnetic nanoparticles which inevitably involve some drawbacks like aglommeration and insufficient magnetic response. In this sense, cytocompatibility/cytotoxicity tests were performed on human cells, and the results have clearly indicated that SCMIOPs are cytocompatible for healthy cell lines HaCaT (human keratinocytes) and HEMa (primary epidermal melanocytes) and cytotoxic for neoplastic cell lines A375 (human melanoma) and B164A5 (murine melanoma) in a dose-dependent manner.